If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 = 2 + (2x + -7) Reorder the terms: 2 + 3x = 2 + (2x + -7) Reorder the terms: 2 + 3x = 2 + (-7 + 2x) Remove parenthesis around (-7 + 2x) 2 + 3x = 2 + -7 + 2x Combine like terms: 2 + -7 = -5 2 + 3x = -5 + 2x Solving 2 + 3x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 3x + -2x = -5 + 2x + -2x Combine like terms: 3x + -2x = 1x 2 + 1x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 1x = -5 + 0 2 + 1x = -5 Add '-2' to each side of the equation. 2 + -2 + 1x = -5 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -5 + -2 1x = -5 + -2 Combine like terms: -5 + -2 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| -4(2x+8)=8x | | X^2+x+7.5=0 | | -4+10[6x-7(8+3x)]= | | 420a=15 | | 4t+8j=10 | | 20-32=s | | -3(-2x+1)=-7x+5 | | 6x+5=-10+6x | | 4(3c+1)+2=3(2c+2)+7 | | 7(-1)-4y=-10 | | -3+4+4n+5=-2n+5n | | 8w^2+10w^3=0 | | 2cosx+secx=7 | | 2p-196=14p+182 | | -5(x-8)=-4(x+7) | | 12x+6=6+12x | | 3.5a=14 | | 6-(-6)=x | | -3x+18=7x-2 | | 3y-3+4y=7 | | 6-(-18)=x | | 2x^2+-x+-3=0 | | m+7=22 | | 6+(-18)=x | | 16x^2+8xy+y^2= | | y=-3x+18 | | 28=4y-6 | | 2m+7=22 | | (6x-2)=56 | | A-3.5=14 | | 5x^2+17x+-12=0 | | e^6x=13 |